Urban Greening Regulations in India: Status and Future Approaches - Gairola, Suresh Chandra (Indian Forester, 2013)
People's increasing awareness about loss of green cover and its impact on climate change, human health and general well-being has brought the issue of urban greening regulations into prominence. This paper examines the evolution and effectiveness of existing regulatory framework related to urban greening issues in India. The limitations and reasons for only partial success of the existing regulations are studied. The role of various agencies like central government, state governments, municipal authorities, non-governmental organisations, voluntary agencies and civil societies in improvement of urban environment is focused. The limitations of the existing regulations related to planting, maintenance and cutting of trees as in existence in various prominent states is analysed. The study reveals that urban greening lacks coordination, focus and priority in planning and implementation at national and regional level. Town planning norms for greening are not followed. The emphasis is primarily on regulating tree cutting rather than involving the stakeholders and civil society in creation and maintenance of additional green cover.